Node.js, Express and MongoDB Dev to deployment - Traversy, Brad (Packt Publishing, 2018)
"You will learn how to structure your Node/Express applications, create data models, relate data, display views, authenticate users, create helpers and much more. Project 1 - Vidjot An application where content creators can register and jot down and manage ideas for future videos. The first project is quite simple as it is meant to be an introduction where the author explains everything about Express routing, middleware, templates, Mongoose, and so on. We implement Passport and a local strategy where we store emails as user names and encrypted passwords in our database. We will prepare and deploy this app to Heroku and add a domain name. Project 2 - Storybooks: A much more sophisticated project. A social network for creating public and private stories. This app uses a Google OAuth 2.0 strategy for authentication. Users can login and create stories which can be set to public or private. They can also choose if comments are allowed to be posted. We will create a dashboard for users to manage their stories. We will create helpers for authentication and access control as well as handlebars template helpers. We will prepare and deploy this app to Heroku and add a domain name."--Resource description page